Translation of a community palliative care intervention: Experience from West Bengal, India - Vijay, Devi (Wellcome Open Res, 2018)
Background: The community form of palliative care first constructed in Kerala, India has gained recognition worldwide. Although it is the subject of important claims about its replicability elsewhere, little effort has gone into studying how this might occur. Drawing on translation studies, we attend to under-examined aspects of the transfer of a community palliative care intervention into a new geographic and institutional context. Methods: Over a period of 29 months, we conducted an in-depth case study of Sanjeevani, a community-based palliative care organization in Nadia district, West Bengal (India), that is modelled on the Kerala approach. We draw upon primary (semi-structured interviews and field notes) and secondary data sources. Results: We identify the translator’s symbolic power and how it counteracts the organizational challenges relating to socio-economic conditions and weak histories of civil society organizing. We find that unlike the Kerala form, which is typified by horizontal linkages and consensus-oriented decision-making, the translated organizational form in Nadia is a hybrid of horizontal and vertical solidarities. We show how translation is an ongoing, dynamic process, where community participation is infused with values of occupational prestige and camaraderie and shaped by emergent vertical solidarities among members. Conclusions: Our findings have implications for how we understand the relationship between locations, institutional histories, and healthcare interventions. We contribute to translation studies in healthcare, and particularly to conversations about the transfer or ‘roll out’ of palliative care interventions from one geography to another.